Asthma control — Practical suggestions for practicing doctors in family practice - Robin J. Green; Refiloe Masekela; Thaneshvari Moodley; Omolemo Kitchin (South African Family Practice)
Many surveys of asthma care suggest that only 5% of asthmatics are meeting the ‘Goals of asthma management’ as set out in the Global Initiative for Asthma (GINA) guidelines. Despite the availability of useful asthma therapies and treatment strategies, the morbidity from asthma has remained significant. This review includes practical suggestions on optimal asthma control for the family practitioner.